2012
DOI: 10.1371/journal.pone.0051555
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Interacting Partners of Sirtuin6

Abstract: SIRT6 is a member of the Sirtuin family of histone deacetylases that has been implicated in inflammatory, aging and metabolic pathways. Some of its actions have been suggested to be via physical interaction with NFκB and HIF1α and transcriptional regulation through its histone deacetylase activity. Our previous studies have investigated the histone deacetylase activity of SIRT6 and explored its ability to regulate the transcriptional responses to an inflammatory stimulus such as TNFα. In order to develop a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 60 publications
2
19
0
Order By: Relevance
“…PARP1 and C-terminal binding protein interacting protein). We also detected the recently reported MYBBP1A (known RelA/p65 interactor) and SMARCA5 (linked to chromatin remodeling) SIRT6 associations (38); however, these interactions did not pass our specificity criteria and were excluded from the final network.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…PARP1 and C-terminal binding protein interacting protein). We also detected the recently reported MYBBP1A (known RelA/p65 interactor) and SMARCA5 (linked to chromatin remodeling) SIRT6 associations (38); however, these interactions did not pass our specificity criteria and were excluded from the final network.…”
Section: Discussionmentioning
confidence: 95%
“…This has revealed the C-terminal binding protein interacting protein, involved in double-strand DNA break repair, and poly-[ADP-ribose] polymerase 1 (PARP1) as SIRT6 non-histone substrates. Other known interactions include DNA-PKcs (35), RelA/p65, and TDG, TSPYL2, and PIAS1 (38), suggesting SIRT6 functions in DNA repair, cell cycle regulation, and NF-kB transcription. However, further knowledge of SIRT6 protein associations and/or substrates is required in order for SIRT6 functions to be explored and relevant molecular mechanisms and regulatory factors to be characterized.…”
mentioning
confidence: 99%
“…SIRT6 is highly expressed in thymus, skeletal, brain and muscle tissues [24, 25]. SIRT6 has two major biochemical activities, functioning as (1) a deacetylase and (2) a mono-ADP ribosyltransferase [26, 27]. SIRT6 participates in numerous biological processes, including maintaining genomic stability, modulating senescence and development of age-related diseases [8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…27 Recent studies have identified direct binding of CDA1 by its N terminus to SIRT6 (Sirtuin 6), a histone deacetylase known to be involved in inflammatory signaling and cell cycle regulation. 28 Indeed, recent studies have shown that SIRT6 overexpression is able to antagonize TGF-b-mediated senescence in human bronchial epithelial cells. 29 The mechanism by which CDA1 deletion attenuates TGF-b signaling in the kidney is a matter of ongoing investigation.…”
Section: Discussionmentioning
confidence: 99%